Part (a)
h(x) = 4*f(x) + 3*g(x)
h ' (x) = d/dx[ 4*f(x) + 3*g(x)]
h ' (x) = d/dx[ 4*f(x) ] + d/dx[ 3*g(x)] ... sum rule
h ' (x) = 4*d/dx[ f(x) ] + 3*d/dx[ g(x)] ... constant multiple rule
h ' (x) = 4*f ' (x) + 3*g ' (x)
h ' (2) = 4*f ' (2) + 3*g ' (2) ... plug in x = 2
h ' (2) = 4*(-2) + 3*(3) ... substitution
h ' (2) = 1
Answer: 1
=======================================================
Part (b)
h(x) = f(x)*g(x)
h ' (x) = f ' (x)*g(x) + f(x)*g ' (x) ... product rule
h ' (2) = f ' (2)*g(2) + f(2)*g ' (2) ... plug in x = 2
h ' (2) = -2*5 + (-4)*3 ... substitution
h ' (2) = -22
Answer: -22
=======================================================
Part (c)
h(x) = f(x)/g(x)
h(x) = [f ' (x)*g(x) - g ' (x)*f(x)]/[ (g(x))^2 ] ... quotient rule
h(2) = [f ' (2)*g(2) - g ' (2)*f(2)]/[ (g(2))^2 ] ... plug in x = 2
h(2) = [-2*5 - 3*(-4)]/[ (5)^2 ] ... substitution
h(2) = 2/25
Answer: 2/25
=======================================================
Part (d)
k(x) = 1 + f(x) ... helps simplify the denominator
k(2) = 1 + f(2) ... plug in x = 2
k(2) = 1 + (-4) ... substitution
k(2) = -3
------
k(x) = 1 + f(x)
k ' (x) = 0 + f ' (x)
k ' (x) = f ' (x)
k ' (2) = f ' (2) ... plug in x = 2
k ' (2) = -2
------
h(x) = g(x)/(1 + f(x))
h(x) = g(x)/k(x)
h ' (x) = [g ' (x)*k(x) - k ' (x)*g(x)]/[ (k(x))^2 ] ... quotient rule
h ' (2) = [g ' (2)*k(2) - k ' (2)*g(2)]/[ (k(2))^2 ] ... plug in x = 2
h ' (2) = [3*(-3) - (-2)*5]/[ (-3)^2 ] ... substitution
h ' (2) = 1/9
Answer: 1/9